Etnosains sebagai Sumber Belajar di Sekolah Dasar - Kelana, Jajang Bayu; Wardani, Duhita Savira; Wulandari, Medita Ayu (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The culture that is owned by a community has a unique knowledge value (local wisdom). The fruit of thought from a culture needs to be preserved as early as possible to preserve the existing history, efforts that can be made are the application of ethnoscience as a learning resource in elementary schools. Past research on this topic was categorized and compared. The method used is a literature review with a sample of 12 articles indexed on Google Scholar in the last 5 years (2015-2020). The discussion on this topic is analyzed comprehensively. The results showed that there were various applications of ethnoscience in learning. This study is to provide an overview and important information about ethnoscience towards learning in elementary schools and also as a reference for further research.